MONETARY AND BANKING SYSTEMS OF THE CENTRAL EURASIAN COUNTRIES IN THE CONTEXT OF THE WORLD FINANCIAL AND ECONOMIC CRISIS - ISMAILOV, Eldar (CENTRAL ASIA AND THE CAUCASUS, 2009)
The financial crisis that has shaken the world dealt a rather hard-felt blow to the economy of the Central Eurasian countries, thus aggravating its weaknesses and ailments. Some countries in this group are keenly feeling the consequences, which are expressed primarily in imbalances in their monetary and banking systems, as well as in decreased trade, tougher conditions for acquiring funds in the world financial market, and so on. The independence of the market economies of the Central European states has made it possible for different scenarios to be enacted for developing and integrating the above-mentioned systems in conditions of financial globalization. Various opinions are being expressed on this account, thus making this a pertinent research topic in the context of the growing dynamism of the processes designed to achieve closer cooperation in the financial and currency spheres.